2011
DOI: 10.1016/j.jvs.2010.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde migration and endovascular retrieval of a venous bullet embolus

Abstract: Venous bullet embolism is a rare and complicated occurrence reported in approximately 0.3% of penetrating trauma. The management of bullet emboli is decided on a case-by-case basis, balancing the risk of the embolus itself against those associated with extraction. We report a case of a 19-year-old man who sustained a gunshot wound to the anterior chest, which migrated to the left internal iliac vein in a retrograde fashion. We were able to successfully retrieve the missile using an endovascular approach, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 8 publications
0
33
0
2
Order By: Relevance
“…Foreign body emboli include needles, bullets, and other projectile objects. The risk of a bullet lodging in the vascular system in penetrating trauma patients is *0.3 % [11]. Approximately, 80 % of foreign body or bullet emboli are arterial (systemic or pulmonary) [7] and the remaining emboli are venous [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foreign body emboli include needles, bullets, and other projectile objects. The risk of a bullet lodging in the vascular system in penetrating trauma patients is *0.3 % [11]. Approximately, 80 % of foreign body or bullet emboli are arterial (systemic or pulmonary) [7] and the remaining emboli are venous [4].…”
Section: Discussionmentioning
confidence: 99%
“…Survival is contingent upon rapid diagnosis and treatment of major injuries [2]. Embolization of traumatic foreign bodies is even more uncommon [3][4][5][6][7][8][9][10][11][12][13]. Recently, we successfully treated a patient with penetrating cardiac trauma with embolization of a foreign body to the pulmonary circulation without major operative intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The guns and ammunition used in a trauma are also important to identify, because bullet emboli are more common with smaller, blunt-nosed, short-length, or low-velocity bullets [1]. Patel et al [8] have concluded that the low incidence of bullet embolism is because two major prerequisites need to be satisfied for a projectile to become an embolus.…”
Section: Discussionmentioning
confidence: 99%
“…Bullet emboli are rare complications of gunshot injuries [1]. The relative rarity of the condition, along with potential lack of early symptoms, often leads to significant delay in diagnosis and treatment of the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the authors recommended surgical removal of the bullet. Moreover, the evolution of endovascular techniques has introduced a new, less invasive therapeutic method [12]. …”
Section: Discussionmentioning
confidence: 99%